Pengaruh Kualitas Pelayanan dan Kepercayaan Merek Terhadap Proses Keputusan Pembelian Asuransi Jiwa Di PT BNILife Insurancae (studi kasus pada nasabah Bank BNI KK Grand Wisata) - Sisilia Manorek, Ike; Maulina, Anita; Arizona Bandi, Anisa (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This Research Aims To Know The Influence Of Service Quality And Brand Trust On The Life Insurance Purchase Decision Process At Pt Bnilife Insurance (Case Study on Customers of Bank Bni Kk Grand Wisata), The research method used is quantitative method. Data collection techniques used in the form of questionnaires and literature. The population in this research is BNI KK Grand Wisata Bekasi customers who buy BNILIFE life insurance products. Sampling used by using random samples or random samples, taking the sample the researcher